The Post-Crisis Sequencing of Economic Integration in Asia: Trade as a Complement to a Monetary Future - Michael G. Plummer; Ganeshan Wignaraja (Asian Development Bank (ADB), 2007)
Bilateral and regional cooperation initiatives in Asia have been growing in importance over the last five years.These accords span the real and financial sectors; rather than following the more typical pattern of "trade first,money later", recent policy initiatives involve the simultaneous implementation of trade and monetary/financial accords. Given this sequence, is there a case for monetary union in East Asia? Is there a case for expanded free-trade areas (FTAs) in the region? This paper attempts to answer these questions using a variety of empirical techniques, including a Computational General Equilibrium (CGE) model, to evaluate the economics of monetary/financial integration and various configurations of FTAs in Asia. We conclude that, at present, the postsequencing of economic integration in Asia is developing such that trade agreements will ultimately complement the movement toward financial and monetary integration. While the political constraint on monetary union is real,it is argued that FTAs should help relax this constraint, adding a political complement to the trade complement.
hdl:11540/1852
Keywords: F15; F36; F42; 330; Economic Integration; Asian Free-Trade Areas; Monetary Union; Trade Policy